A Review of the Blended Learning as the Model in Improving Students` Paragraph Writing Skills - Dewi Safira Maulida; M Arinal Rahman; Ciptro Handrianto; Shahid Rasool (Abjadia, 2022)
Academics have spent many years investigating the connection between blended learning and various other instructional approaches. On the other hand, there are only a few pertinent journal articles on the impact of content assessment on the integrated effect of the blended learning model. Therefore, this conceptual paper aims to identify patterns in L2 research on paragraph writing skills to understand better the advantages and disadvantages of using Blended learning for language learning. This research used the literature review method to synthesize several previously published publications to understand the notion of blended learning as it relates to paragraph writing abilities. The primary parts of this article are broken up into two different parts. The author begins by defending the need for a course in paragraph writing skills within the L2 learning environment. Second, an analysis of the studies that were looked over is performed to highlight the pertinent benefits and limitations of blended learning for the learning of paragraph writing. The findings of this study could be applied to additional research in the future to determine whether or not the Blended Learning methodology has an impact on students' capacity to compose paragraphs.